2013
DOI: 10.1080/10408398.2012.689380
|View full text |Cite
|
Sign up to set email alerts
|

Principles and Limitations of Stable Isotopes in Differentiating Organic and Conventional Foodstuffs: 1. Plant Products

Abstract: Among the lighter elements having two or more stable isotopes (H, C, N, O, S), δ(15)N appears to be the most promising isotopic marker to differentiate plant products from conventional and organic farms. Organic plant products vary within a range of δ(15)N values of +0.3 to +14.6%, while conventional plant products range from negative to positive values, i.e. -4.0 to +8.7%. The main factors affecting δ(15)N signatures of plants are N fertilizers, biological N2 fixation, plant organs and plant age. Correlations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
59
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 80 publications
2
59
1
Order By: Relevance
“…multi‐elemental analysis and/or stable isotope analysis of several light or heavy mass elements including H, C, N, O, S and Sr, 1 H‐NMR profiling and near‐infrared reflectance spectroscopy. Only a limited number of studies have focused on discriminating organic and conventional wheat (both bread and durum) and cereals in general …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…multi‐elemental analysis and/or stable isotope analysis of several light or heavy mass elements including H, C, N, O, S and Sr, 1 H‐NMR profiling and near‐infrared reflectance spectroscopy. Only a limited number of studies have focused on discriminating organic and conventional wheat (both bread and durum) and cereals in general …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the use of δ 15 N for organic authentication is challenged by the fact that N 2 ‐fixing plants (the Leguminosae family ) have δ 15 N values overlapping with the range of synthetic fertilizers and are frequently used as cover crops or green manures in organic crop rotations. Several studies have thus demonstrated that δ 15 N as a single parameter does not enable authenticity testing of organic plant products in all real‐life situations . To eliminate this problem, oxygen isotope analysis of nitrate has been utilized in a few studies .…”
Section: Introductionmentioning
confidence: 99%
“…After that, transpiration through the leaf stomata occurs, leading to enrichment of δ 18 O in the leaf water. 29 The distribution trends of δ 18 O values in garlic samples is similar to that observed in Slovenian groundwater, 30 when considering the δ 18 O content of groundwater in the Mediterranean re- Mean ± SD -26.9 ± 0.7 6.5 ± 2.6 1. gion and in garlic samples from this region (Fig. 2).…”
mentioning
confidence: 52%
“…The use of stable isotopes to differentiate organic vs. conventional plant and animal products was reviewed by Inácio & Chalk (2015) and Inácio et al (2015a), respectively. In a study of conventionally and organically produced lettuce (Lactuca sativa L.) in the state of Rio de Janeiro, Inácio et al (2015b) concluded that the δ 15 N signatures of lettuce were an indicator of the principal N inputs (BNF, organic or manufactured fertilizer) instead of a definitive indicator of the production regime.…”
Section: Production Regimementioning
confidence: 99%